2006
DOI: 10.1007/s10522-006-9042-x
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary heterogeneity model of late-life fecundity in Drosophila

Abstract: There is now a significant body of research that establishes the deceleration of mortality rates in late life and their ultimate leveling off on a late-life plateau. Natural selection has been offered as one mechanism responsible for these plateaus. The force of natural selection should also exert such effects on female fecundity. We have already developed a model of female fecundity in late life that incorporates the general predictions of the evolutionary model. The original evolutionary model predicts a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…Age-specific fecundity for two populations of D. melanogaster subject to different demographic selection regimes. Mean fecundity for the early reproducing ACO (circles) and late reproducing CO (triangles) females are shown along with a fitted regression (solid line) based on the evolutionary heterogeneity model of female fecundity (Mueller et al 2007). The estimated ages at which the fecundity plateaus begin are shown with arrows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Age-specific fecundity for two populations of D. melanogaster subject to different demographic selection regimes. Mean fecundity for the early reproducing ACO (circles) and late reproducing CO (triangles) females are shown along with a fitted regression (solid line) based on the evolutionary heterogeneity model of female fecundity (Mueller et al 2007). The estimated ages at which the fecundity plateaus begin are shown with arrows.…”
Section: Resultsmentioning
confidence: 99%
“…particular, evolutionary theory suggests that fecundity should plateau sometime after the last age of survival in a population's evolutionary history. In several independent experiments, Rauser et al (2003Rauser et al ( , 2006b and Mueller et al (2007) found late-life fecundity plateaus in populations of D. melanogaster. More notably, they found statistically significant differences in the days at which late-life fecundity plateaued in populations with different last ages of reproduction in their recent evolutionary history (figure 6; Rauser et al 2006b).…”
Section: -2006: First Deliberate Laboratory Evolution Of Late Lifementioning
confidence: 98%
See 1 more Smart Citation
“…In that regard, a relatively new demographic phenomenon has emerged; the rate of increase in death rates at older ages has slowed in developed countries. It has also been observed in non-human populations (Mueller et al 2007). This so-called ''mortality plateau'' is a violation of the invariant increase in death rates predicted by traditional models like the Gompertz.…”
Section: Demographic Tangentmentioning
confidence: 72%
“…Some of the major factors comprising epigenetic modulators are prenatal maternal health, nutritional and hormonal status, and postnatal access to nutrition and exposure to viruses, bacteria and other germs, especially until and around the age of puberty. 17,[48][49][50][51] Therefore, an ideal strategy for the prevention or modulation of aging for extended health span incorporates genetic and epigenetic interventions. Defective or inefficient genetic pathways, which either lead to the emergence of specific diseases or significantly enhance the chances of a disease surely require successful application of the main stream gene therapy approaches including stem cells.…”
Section: Gene Therapy In Aging Also Involves Epigenetic Interventionsmentioning
confidence: 99%